2016
DOI: 10.1111/1365-2664.12790
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing management to enhance multifunctionality in a boreal forest landscape

Abstract: Summary1. The boreal biome, representing approximately one third of remaining global forests, provides a number of crucial ecosystem services. A particular challenge in forest ecosystems is to reconcile demand for increased timber production with provisioning of other ecosystem services and biodiversity. However, there is still little knowledge about how forest management could help solve this challenge. Hence, studies that investigate how to manage forests to reduce trade-offs between ecosystem services and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 51 publications
2
98
0
2
Order By: Relevance
“…Boreal forests are one of the biggest terrestrial carbon pools on Earth [2,3], storing carbon in the tree biomass and releasing it through decomposition, therefore playing a significant role in global climate change mitigation [4,5]. With increasing interest to promote carbon sequestration in forests, various new forest management practices are employed in managed even-aged stands [6][7][8][9] to meet the climate change targets and to reduce the carbon dioxide emissions in land use, land use change, and forestry (LULUCF) sector [1,10]. However, there is still a lack of reference studies of unmanaged over-mature forests [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boreal forests are one of the biggest terrestrial carbon pools on Earth [2,3], storing carbon in the tree biomass and releasing it through decomposition, therefore playing a significant role in global climate change mitigation [4,5]. With increasing interest to promote carbon sequestration in forests, various new forest management practices are employed in managed even-aged stands [6][7][8][9] to meet the climate change targets and to reduce the carbon dioxide emissions in land use, land use change, and forestry (LULUCF) sector [1,10]. However, there is still a lack of reference studies of unmanaged over-mature forests [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to the national forest inventory, Norway spruce forests constitute 20% of the forest standing volume in Latvia, also being one of the most economically important and intensively managed tree species [25]. As sustainable forest management is considered the most efficient way to increase the forest carbon stock [9,20], there is a growing need for reference data from unmanaged spruce stands. Therefore, the aim of this study was to quantify hemiboreal old unmanaged Norway spruce forests carbon stock in the main carbon pools: tree biomass, deadwood, and soil organic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…; Triviño et al . ). Our hope is that societies around the world can benefit from the wealth of such observational, experimental and theoretical works in forest ecosystems to help realize sustainable forest management.…”
Section: Special Focuses: Forest Biodiversity and Ecosystem Services mentioning
confidence: 97%
“…This finding is supported by the extensive review by Abson et al (2014), who reported ecosystem service literature from forest ecosystems to be focused on tropical forests. Few, model-based studies have examined the effects of boreal forest management on ecosystem services (Miina et al 2010;Zanchi et al 2014;Triviño et al 2017), but the set of ecosystem services included also in these studies is limited compared to the wide range of benefits that boreal forests provide. It is clear that the existing literature, particularly literature building on the ecosystem services framework, does not yet cover the full range of boreal forestry's potential consequences for human benefits.…”
Section: Ecosystem Services and Boreal Forestry In Existing Literaturementioning
confidence: 99%
“…Kuuluvainen et al 2012) and care in the application of management activities to explicitly target multiple ecosystem services (e.g. Triviño et al 2017).Even though there is a long research tradition of linking forestry with ecosystem functioning, the terminology of ecosystem services has so far been used only marginally in the context of assessing the environmental impacts of boreal forestry. This is contrary to its common adoption in policy (e.g.…”
mentioning
confidence: 99%